Finish line for full coverage crown: A systematic review - Eri H. Jubhari; Edwina Lesal (DiscoverSys Inc., 2021)
Objective: To find the mostly used type of finish line for each types of full coverage crown.Methods: an initial search was conducted from PubMed database and Wiley Online Library to evaluate article about finish line and material types of full coverage crown. The keywords used were “finish line” and “fixed prosthodontics”. The initial results of this search were 175 articles. Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines and Population/Problem, Intervention, Comparison/Control, and Outcome (PICO) questions were used for manual selection. After manual selection, there were only 4 articles that met the inclusion criteria, focusing on the number of each type of materials for full coverage crown.Results: From these 4 articles, two were in vivo study and another two were in vitro study, with a total samples 140. The samples used in those articles were all-ceramic, all-metal, and zirconia crowns. Two articles did not mention about instrument (bur) and only 3 articles mention about impression materials.Conclusion: in all-metal and all-ceramic crown articles, chamfer finish line were mostly used, but, in zirconia crown article, both rounded shoulder and shoulder-less/knife-edge were equally used.